A primary care pharmacogenetic precision medicine pilot based on specific Māori tribal ethical frameworks and principles - Stephen P. Robertson; Benjamin J. Halliday; Rhonda Tibble; Caroline Koia; Tuta Haereroa; Elizabeth Goodin; Ben Curran; Claire E. Rye; Helen Wihongi; Ben Te Aika; Joep de Ligt; Donia Macartney-Coxson; et al. (Journal of Community Genetics, 2026)
Indigenous tribal communities are frequently underserved by genomic medicine because they are under-represented in research, often live in remote locations and have ethical and cultural perspectives that vary from westernised standpoints. The Rakeiora platform, a permissioning and analytical environment that incorporates Māori perspectives and ethical frameworks on how precision medicine research is best conducted was used to host a pharmacogenetic exemplar project to demonstrate proof of principle in a tribal community. The project was prospectively co-designed alongside community representatives through an extensive series of kanohi ki te kanohi (face-to-face) consultation hui, drawing on the strengths, insights, and aspirations of the community. Narratives socialising the study were metaphorically located in tribal-specific histories to improve participation. The cohort of 148 Māori individuals consented to have variants in CYP2C19 extracted from whole genome sequence datasets and correlated to the medicines they were prescribed and had dispensed over a 12-month period. Genotyping indicated that 7% of the cohort were genotypically predicted to be “poor metabolisers” and 11% “rapid metabolisers” of at least one drug known to be processed by CYP2C19. Based on international guidelines, 40% of prescriptions could have benefited from knowledge of the participant’s CYP2C19 genotype through either dose adjustment or prescription of an alternative drug. The study population was broadly supportive of research into precision medicine, but the majority wished to retain ongoing dynamic consent practices mediated by trusted local figures.